PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN MERAUKE PROPINSI PAPUA - Elisabeth Pruwo Gebze; Mahlia Muis; Maat Pono (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine the influence of leadership style, work discipline and motivation on the performance of employees at the Social Service in Merauke District of Papua Province. The type of this research is quantitative research that is to know and analyze the influence of leadership style, work discipline and motivation to the performance of Social Service of Merauke Regency of Papua Province. The results of this study found that leadership style negatively and significantly influence on performance, work discipline positively and significantly influence on employee performance, motivation has positive and insignificant effect on employee performance. Work Discipline Affects the Dominant positively and significantly to the performance of employees of the Social Service of Merauke Regency of Papua Province